E-PROMOTION BIDANG PARIWISATA DI PROVINSI RIAU MELALUI PROGRAM CBC DAN PROGRAM RCC - Ningsih Rafika Duri; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Cerita Baru Centre (CBC) and Riau Creative Centre (RCC) is a program created by the Riau Province Tourism Office with the aim of promoting leading tourism potential which has been the main attraction of Riau tourism in the hope of increasing the number of domestic and foreign tourists visiting. The purpose of this study was to find out how the promotion of tourism sector innovation in Riau Province as well as what were the inhibiting factors of the promotion of innovation through the CBC program and the RCC program. The theoretical concept used in this study is the promotion of innovation by Kotler and Keller which consists of: advertising, sales promotion, events, publicity, and media. This research is a qualitative study with a case study approach. The selection of informants used purposive sampling technique. The technique of collecting data through observation, interviews and documentation. The results of this study indicate that the promotion of innovation in tourism in Riau Province through the CBC program and the RCC program has been carried out but has not run optimally. This is due to the existence of factors that inhibit the promotion of innovation which include: budget, and human resources. Should, tourism office of Riau Province responsible for RCC program can pay more attention goals and objectives program already predetermined and review the program that have been carried out.Keywords: E-Promotion, Tourism, CBC Program, RCC Program